Implementasi SIPD dalam Mendukung Relevansi Laporan Pengelolaan Anggaran di Dispora Kabupaten Gianyar - Gusti Ayu Monika; I Wayan Sudiana; Ni Made Wisni Arie Pramuki (Hita Akuntansi dan Keuangan, 2026)
This study examines the implementation of the Regional Government Information System (SIPD), its contribution to enhancing the relevance of budget management reports, and the challenges encountered during its application at the Department of Youth and Sports (Dispora) of Gianyar Regency. A descriptive qualitative approach was employed to gain an in-depth understanding of the phenomenon. Data were obtained through observations, in-depth interviews with key informants, and documentation review. The analysis followed the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that SIPD has been applied throughout the entire budget management cycle, including planning, execution, and reporting processes. The system improves the relevance of financial reports by providing information that supports feedback, predictive insights, and timely decision-making. Nevertheless, its implementation is not without limitations, particularly related to human resource competencies, technical system disruptions, and reliance on stable internet access. Overall, SIPD contributes positively to improving the relevance of budget management reports; however, continuous system refinement and capacity building are required to achieve optimal performance.